Karl Polanyi: The Limits of the Market - By Gareth Dale - Langton, Robert W. (Political Studies Review, 2012)
The article reviews the book "Karl Polanyi: The Limits of the Market," by Gareth Dale.
Keywords: DALE, Gareth; Karl Polanyi: The Limits of the Market (Book); book review; nonfiction